Costs and use of antimigraine drugs in Italy: a ten-year analysis of national data - Luigi Francesco Iannone; Marina Romozzi; Paolo Calabresi; Roberto De Icco; Raffaele Ornello; Cristina Tassorelli; Simona Sacco; Pierangelo Geppetti (The European Journal of Health Economics, 2026)
Abstract Background Migraine is a highly prevalent neurological disorder associated with substantial disability and economic burden. Considering the recent introduction of anti-calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs), expenditure analysis are needed to evaluate a rapidly evolving therapeutic field. Therefore, we analyzed national pharmaco-utilization trends of antimigraine drugs in Italy over the decade 2014–2023 using publicly available data from the “ Osservatorio Nazionale sull’Impiego dei Medicinali ” (OsMed) report of the Italian Medicines Agency (AIFA). Methods All antimigraine drugs reimbursed by the National Health Service and classified under the antimigraine drug group were included. Indicators comprised defined daily doses (DDD) per 1,000 inhabitants per day, per-capita expenditure, cost per DDD, and user-level measures. Results In 2023, 0.6% of the Italian population received antimigraine drugs, with a median age of 51 years and a marked female predominance. National expenditure reached €92 million, corresponding to €1.56 per capita and 0.4% of pharmaceutical spending, with consumption of 1.2 DDD/1,000 inhabitants per day. Triptans accounted for 65% of costs and 75% of use, remaining the dominant class. Anti-CGRP mAbs, introduced in 2019, rapidly expanded to represent 35% of expenditure in 2023, with the highest cost per DDD. Historical classes such as ergot alkaloids and other antimigraine agents declined to negligible levels. Over the decade, consumption increased modestly (compound annual growth rate + 3.1%) while expenditure rose more slowly (+ 1.5%), with costs escalation after the introduction of anti-CGRP mAbs. Of note, the overall expending for novel anti-CGRP drugs remains limited when considering the high prevalence of migraine. Conclusions These findings highlight the evolving therapeutic scenario of migraine in Italy, the impact of innovation on budget, and the need for real-world studies integrating pharmaco-utilization, direct and indirect costs and clinical outcomes.